The Effects of Soft Skills, Personal Attributes, and Work Readiness on the Employability of Fresh Graduates at the Faculty of Economics and Business, University of Mataram - Rina Agustina; Mukmin Suryatni (Danadyaksa: Post Modern Economy Journal, 2026)
Employability has become a critical issue for fresh graduates, particularly in facing increasingly competitive labor market demands. This study aims to examine the effect of soft skills, personal attributes, and job readiness on the employability of fresh graduates from the Faculty of Economics and Business, University of Mataram. Employability is conceptualized as the ability of graduates to obtain, maintain, and adapt to employment opportunities in a dynamic work environment. This research adopts a quantitative approach using a survey method. The population consists of fresh graduates of the Faculty of Economics and Business, University of Mataram, with samples selected using purposive sampling techniques. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, classical assumption tests were conducted, including normality, multicollinearity, and heteroscedasticity tests, to ensure the validity of the regression model. The results indicate that soft skills have a positive and significant effect on employability, highlighting the importance of communication skills, teamwork, adaptability, and problem-solving abilities in enhancing graduates’ competitiveness. Personal attributes, including self-confidence, responsibility, and emotional control, are also found to have a significant positive effect on employability. Furthermore, job readiness significantly influences employability, suggesting that graduates who are better prepared mentally, cognitively, and behaviorally are more capable of meeting workplace expectations. Simultaneously, soft skills, personal attributes, and job readiness significantly affect employability. These findings emphasize the need for higher education institutions to strengthen the development of soft skills, personal attributes, and job readiness to improve graduate employability and facilitate a smoother transition into the workplace.